THE IMPACT OF HEALTH-IMPROVING TECHNOLOGY ON ELEMENTARY SCHOOL CHILDREN - Shuba Liudmyla; Shuba Victoria; Shuba Victor (Alfred Nobel University Publisher, 2023)
The well-being of a child reflects their ability to withstand challenging and harmful factors, and their stability is determined by achieving a balance in key physiological functions during their development. According to the Ministry of Health of Ukraine, approximately 90 percent of children exhibit various health deviations, with over 59 percent experiencing poor physical condition. The health of children can be viewed as a dynamic and functional state, serving as an indicator of their everyday effectiveness. Furthermore, it can provide insights into their lifestyle choices and personal interests. Physical education in the field of education is guided by established educational standards that are approved in accordance with the law. These standards aim to provide scientifically-based guidelines for physical activity for children and young people, taking into account their health status and level of physical development. Health is a fundamental aspect of an individual's well-being and greatly influences their overall quality of life. Currently, Ukraine is experiencing a high level of morbidity, particularly among children and adolescents. Specifically, during the schooling years, there is a significant decline in the number of healthy children from the first to the eleventh grade, with a decrease of 3-4 times. The inadequate level of physical fitness among young Ukrainians can be attributed, to a large extent, to the lack of significant incentives for the promotion of sports culture among the younger generation. Consequently, the preservation and enhancement of students' health, the promotion of physical activity, and the development and improvement of fundamental physical attributes become the primary objectives of physical education for elementary school students. These objectives also represent priority areas for the overall development of our society. To achieve these goals, physical education sessions for elementary school students should address health improvement, pedagogical aspects, and educational objectives in a comprehensive manner. Only through a holistic approach can we effectively exert a multifaceted influence on the development and growth of elementary school students. The aim is to investigate the impact of the developed technology on physical fitness levels of 8-9-yearold students. Material: 8- to 9-year-old students took part in the research. Out of the four surveyed classes four homogeneous groups were formed. Experimental groups consisted of 20 boys and 16 girls; control groups consisted of 19 boys, and 17 girls who were classified into the main medical group for health condition. Results. The process of physical education should be organized in a rational manner, aiming for the comprehensive and balanced development of motor qualities. Achieving high levels of physical fitness serves as a functional basis for expanding the repertoire of motor skills and abilities, while significantly enhancing the functional capacity of the body's systems. Motor tests are widely used as a common and accessible method of pedagogical assessment. The subjects' physical preparedness was evaluated through pedagogical testing, which assessed their level of basic motor qualities, including flexibility, strength, endurance, speed, and speed-strength abilities. An increase in the indicators of physical fitness was found in experimental and control groups. But in the experimental groups (boys, girls) - the indicators improved by 46.11%, in the control groups (boys, girls) the indicators improved by 29.76%. Conclusions. The obtained results testify about the effectiveness of technology developed by us, which consisted of two blocks with the priority use of health-improving exercises, as a new tool for the formation of a healthy lifestyle.